Pengaruh Promosi dan Ulasan Produk terhadap Keputusan Pembelian pada Marketplace Shopee: Studi Kasus Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Teuku Umar - Riski Asriandi; Cut Mega Putri; Said Acmad Kabiru Raflie (Indo Publishing, 2026)
This study aims to analyze the influence of promotion and product reviews on purchasing decisions on the Shopee marketplace among students of the Faculty of Economics and Business, Teuku Umar University. This research uses a quantitative approach with an associative design. The population were all active students who had made purchases on Shopee. The sample size was determined using the Cochran formula, resulting in 100 respondents selected through accidental sampling. Data were collected using a questionnaire with a Likert scale and analyzed using multiple linear regression with SPSS. The results showed that promotion has a positive and significant effect on purchasing decisions (t = 3.119; p = 0.002), and product reviews also have a positive and significant effect on purchasing decisions (t = 2.488; p = 0.015). Simultaneously, promotion and product reviews have a significant effect on purchasing decisions (F = 15.438; p = 0.000). The coefficient of determination (R²) of 0.560 indicates that promotion and product reviews explain 56.0% of purchasing decisions, while the remaining 44.0% is explained by other factors. These findings confirm that better promotion and more informative product reviews increase consumer tendency to make purchasing decisions on Shopee.